Effect of bran particle size on rheology properties and baking quality of whole wheat flour from four different varieties. (1st February 2023) - Li, Cheng; Tilley, Michael; Chen, Richard; Siliveru, Kaliramesh; Li, Yonghui
Abstract: The potential health benefits of consuming whole grain foods are increasingly attracting customers' interest. The effect of bran particle size on whole wheat flour (WWF) bread-making performance was investigated using four different varieties with protein levels of 9–15 g/100g. Five different bran particle size ranges from 590.5 to 159.7 μm were obtained using different milling methods. Mixolab tests revealed that white flour had a lower water absorption (56.2–59.2 g/100g) than the corresponding whole wheat flours (63.2–67.0 g/100g). Larger specific loaf volume was observed for white bread with a relatively higher flour protein content, but this was not always associated with the trend for the WWF. For most wheat varieties, the bread from WWF with the fine bran had the lowest specific loaf volume, darker crumb color, and larger hardness value than bread made with white flour or with WWF of other particle sizes. Overall, WWF with medium to coarse bran size was more suitable for bread production. The findings of this study contribute to the standardization of whole flour bran particle sizes for quality assessment and effective industrial production. Highlights: Bran particle size effect on whole wheat flour (WWF) bread-making performance was investigated. Four bread wheat varieties with protein from 9 to 15% were comparatively studied. WWF had greater water absorption but reduced starch retrogradation than white flour. WWF with medium/large size bran produced softer bread with larger loaf specific volume. Modulating bran particle sizes is effective in improving WWF bread-making quality.